Balance sheet-based policies in COVID‑19 fiscal packages: How to improve transparency and risk analysis? - Moretti, Delphine (OECD Publishing, 2021)
This article discusses why the composition of emergency fiscal packages in response to the COVID-19 pandemic make it important for governments to monitor and manage their balance sheets going forward. It analyses current practices with transparency and risk analysis concerning balance sheet-based measures drawn from case studies of nine OECD countries. It then identifies further steps governments should consider to increase transparency and strengthen risk analysis on COVID-19 related balance sheet-based policies that will help to strengthen fiscal frameworks
Keywords: Economics; Finance and Investment; Governance